2015
DOI: 10.1128/jvi.02880-14
|View full text |Cite
|
Sign up to set email alerts
|

BGLF4 Kinase Modulates the Structure and Transport Preference of the Nuclear Pore Complex To Facilitate Nuclear Import of Epstein-Barr Virus Lytic Proteins

Abstract: BGLF4 kinase, the only Ser/Thr protein kinase encoded by the Epstein-Barr virus (EBV) genome, phosphorylates multiple viral and cellular substrates to optimize the cellular environment for viral DNA replication and the nuclear egress of nucleocapsids. Previously, we found that nuclear targeting of BGLF4 is through direct interaction with the FG repeat-containing nucleoporins (FG-Nups) Nup62 and Nup153 independently of cytosolic transport factors. Here, we investigated the regulatory effects of BGLF4 on the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 91 publications
1
45
0
Order By: Relevance
“…(iii) ORF36 might regulate the nuclear translocation of virions. Recently, it was reported that BGLF4 induces the nuclear redistribution of several EBV lytic proteins, including the major capsid protein, VCA (ORF25) (53). Interestingly, the same study found that KSHV ORF36 was also capable of inducing the nuclear translocation of VCA.…”
Section: Discussionmentioning
confidence: 61%
“…(iii) ORF36 might regulate the nuclear translocation of virions. Recently, it was reported that BGLF4 induces the nuclear redistribution of several EBV lytic proteins, including the major capsid protein, VCA (ORF25) (53). Interestingly, the same study found that KSHV ORF36 was also capable of inducing the nuclear translocation of VCA.…”
Section: Discussionmentioning
confidence: 61%
“…Moreover, alternative mechanisms of NEC inhibition could be similarly effective, eg, the inhibitory targeting of NEC phosphorylation. Considering the fact that most if not all of the NEC‐associated proteins undergo phosphorylation, inhibitors of NEC phosphorylation appear likewise attractive for use in antiviral applications . In addition, considering the various structural changes predicted or already proven as a prerequisite for NEC assembly and down‐stream functions, small molecules interfering with conformational switches might be attractive for further development.…”
Section: Discussionmentioning
confidence: 99%
“…113,114 During herpesviral replication, the nuclear lamina is locally distorted, mainly on the basis of a disassembly of lamins A/C induced by the site-specific phosphorylation at Ser22 (in part also Ser392). A number of laminphosphorylating protein kinase activities have been described, including cyclin-dependent kinase (CDK) 1, protein kinase C (PKC), protein TABLE 1 Herpesviral core NEC proteins and NEC-associated proteins Alpha-herpesviruses Beta-herpesviruses Gamma-herpesviruses [78][79][80][81][82][83][84][85][86][87] HSV kinase B, and CDK-like enzymes, including herpesviral protein kinases. 111,113 In addition, the association of further proteins leads to a remodeling and functional alteration of the NE through fine-regulated processes.…”
Section: Concerted Action Between Various Regulatory Proteins Assocmentioning
confidence: 99%
“…In addition, EBV-encoded BGLF4 is a Ser/Thr kinase that can mimic cyclin-dependent kinase 1 to induce several prophase-like phenomena, such as chromosome condensation and partial disassembly of the nuclear lamina, for the nuclear egress of viral nu-cleocapsids (1). BGLF4 also modulates the transport preference of NPCs for the nuclear import of viral components (2).…”
mentioning
confidence: 99%